Analisis Manajemen Risiko Perpustakaan UIN Sunan Gunung Djati Bandung - Nurfauzi, Ilham; Suryani, Ani (Media Pustakawan, 2025)
In its implementation, UIN SGD Bandung Library often encounters obstacles known as risks. Risk management is needed to minimize the occurrence of risks. The study was conducted to analyze the risk management process/stages and to understand the results of risk management, which include identification, sources, levels, and risk mitigation. The study used a qualitative method with a field case study approach, namely in the Technical Services Sector, Library Services Sector, and ICT Sector, with the SNI ISO 31000 framework. Data collection was carried out through interviews, observations, and literature studies. Then, data processing was carried out through the risk assessment stages, which include: risk identification, risk analysis, and risk evaluation, as well as risk treatment/risk mitigation. The results of the study showed that 126 risks were identified, 89 came from internal sources, and 37 came from external sources of the library. In this study, internal sources were more dominant than external sources. Based on the level, 75 are low-level risks, 39 are medium-level risks, and 12 are high-level risks. Various levels of risk influence the implementation of the library, so the mitigation must be carried out immediately based on priority. Risk mitigations are conveyed in the form of recommendations. From the results of the analysis, it can be concluded that the risk management process at the UIN SGD Bandung Library follows the SNI ISO 31000 framework. Various risks that have emerged have been identified, including the source, level, and mitigation recommendation.